Exterior material for power storage device and power storage device
Patent Information
- Application Number
- JP2023026483
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-07-20
- Filing Date
- 2023-02-22
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2039-06-24
AI Technical Summary
【0017】 前項1では、外装材の最外層がポリアミドフィルム、ポリエステルフィルム及びポリオレフィンフィルムからなる群から選択される少なくとも一つからなり、最外層の表面の算術平均高さSaが0.03~0.20μmの範囲であり、山の数が1mm2当たり5~30個の範囲であることから、最外層の表面である外装材の表面は凹凸部が形成されることで高い滑り性を有するとともに、表面積が拡がることで粘着テープとの接着面積が大きくなり、したがって外装材の表面の粘着テープとの密着性についても高い密着性を有する。
Smart Images

Figure 0007635283000002 
Figure 0007635283000003 
Figure 0007635283000004
Abstract
Description
[Technical field]
[0001] The present invention relates to an exterior material for an electricity storage device such as a lithium ion battery, a method for producing the same, and an electricity storage device. [Background technology]
[0002] For example, an exterior material for a lithium-ion battery is made of a laminate film having an outermost layer, a barrier layer, and a sealant layer in a laminated configuration. When a lithium-ion battery is manufactured using this exterior material, the exterior material is formed into a bag shape or a container shape by molding using a molding die, and the lithium-ion battery contents (battery cells, electrolyte, etc.) are accommodated inside and heat sealed.
[0003] When using a lithium-ion battery that uses this exterior material, it is incorporated into a specified circuit or attached to a specified location. At that time, the lithium-ion battery is generally fixed with insulating adhesive tape to prevent the position of the lithium-ion battery from shifting.
[0004] Incidentally, in order to improve the formability and slipperiness of the exterior material and to prevent blocking, lubricants and anti-blocking agents are sometimes present on the surface of conventional exterior materials (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 5652178 Summary of the Invention [Problem to be solved by the invention]
[0006] As described above, when a lubricant or antiblocking agent is present on the surface of the exterior material, the adhesion of the adhesive tape to the surface of the exterior body is reduced, and the adhesive tape may peel off from the surface of the exterior material when the lithium-ion battery is fixed in position with the adhesive tape.
[0007] The present invention has been made in consideration of the above-mentioned technical background, and an object of the present invention is to provide an exterior material for an electricity storage device having a surface that has high slip properties and high adhesion to an adhesive tape. [Means for solving the problem]
[0008] The present inventors have conducted extensive research and investigation into packaging materials for power storage devices, and have found that the outermost layer of the packaging material is made of a specified film, and the surface properties of the outermost layer are such that technique The average height Sa is within a predetermined range and 1 mm 2 It was found that the above object can be achieved so long as the number of winnings is within a predetermined range, and the present invention was completed based on this finding.
[0009] That is, the present invention provides the following means.
[0010] 1) An exterior material for an electricity storage device, comprising an outermost layer, a sealant layer, and a barrier layer disposed between the outermost layer and the sealant layer in a laminated state, the outermost layer is made of at least one selected from the group consisting of a polyamide film, a polyester film, and a polyolefin film, In terms of surface properties of the outermost layer, The arithmetic mean height Sa is in the range of 0.03 to 0.20 μm, The cross-sectional area at a height of +0.1 μm from the reference plane of Sa is 7500 μm 2 If a convex part with a peak or more is defined as a mountain, the number of peaks is 1 mm 2 Exterior material for power storage devices with 5 to 30 pieces per unit.
[0011] 2) When the position of the center of gravity of the cross section of the mountain at a height position of +0.1 μm from the reference plane is defined as the position of the center of gravity of the mountain, 2 2. An exterior material for an electricity storage device according to item 1, wherein the distances between the centers of gravity of adjacent peaks on the exterior material are all within a range of 150 to 700 μm.
[0012] 3) the outermost layer and the barrier layer are bonded with an adhesive layer disposed between the two layers; 3. The exterior packaging material for an electricity storage device according to item 1 or 2 above, wherein a surface of the adhesive layer facing the outermost layer is formed with projections and recesses.
[0013] 4) An exterior material for an electricity storage device as described in 3) above, in which the unevenness formed on the surface of the adhesive layer facing the outermost layer and the unevenness formed on the surface of the outermost layer are approximately aligned.
[0014] 5) A method for producing an exterior material for an electricity storage device according to the preceding item 3 or 4, comprising the steps of: A method for producing an exterior material for an electricity storage device, comprising applying an adhesive to an adhesive layer disposed between an outermost layer and a barrier layer of the exterior material by a gravure coating method.
[0015] 6) An electricity storage device, the contents of which are packaged in the exterior packaging material for an electricity storage device according to any one of items 1 to 4 above. Effect of the Invention
[0016] The present invention provides the following advantages.
[0017] In the above item 1, the outermost layer of the exterior material is made of at least one selected from the group consisting of polyamide film, polyester film, and polyolefin film, and the arithmetic mean height Sa of the surface of the outermost layer is in the range of 0.03 to 0.20 μm, and the number of peaks is 1 mm or less. 2Since the number of particles per unit area is in the range of 5 to 30, the surface of the exterior material, which is the surface of the outermost layer, has high slipperiness due to the formation of uneven parts, and the adhesive area with the adhesive tape is increased due to the increased surface area, and therefore the surface of the exterior material has high adhesion to the adhesive tape.
[0018] In the above items 2 to 4, the slipperiness of the surface of the exterior material can be reliably increased, and the adhesion of the surface of the exterior material to the adhesive tape can also be reliably increased.
[0019] In the above item 5, by applying the adhesive of the adhesive layer onto the barrier layer by gravure coating, it is possible to reliably achieve a predetermined surface property on the surface of the outermost layer of the packaging material for an electricity storage device according to the present invention.
[0020] In the above item 6, it is possible to provide an electricity storage device that can be firmly fixed in position with adhesive tape. [Brief description of the drawings]
[0021] [Figure 1] FIG. 1 is a schematic cross-sectional view of an exterior material for an electricity storage device according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing contour lines at a height of +0.1 μm from the reference plane Sa in a surface irregularity image of the surface of the outermost layer of a packaging material. [Diagram 3] FIG. 3 is a diagram for explaining the distance between the positions of the centers of gravity of adjacent mountains in the schematic diagram shown in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] An embodiment of the present invention will be described below with reference to the drawings.
[0023] As shown in FIG. 1, an exterior material 1 for an electricity storage device according to one embodiment of the present invention is for use in an electricity storage device, such as a lithium ion battery, and is formed into a bag shape like conventional exterior materials or into a container shape by molding using a molding die, and is then heat-sealed after containing the lithium ion battery contents (battery cell, electrolyte, etc.) as the electricity storage device contents.
[0024] As shown in FIG. 1, the exterior packaging material 1 is composed of a laminated film in which an outermost layer 2, a sealant layer 4 as an innermost layer, and a barrier layer 3 disposed between the layers 2, 4 are bonded together.
[0025] Describing the configuration of the exterior packaging material 1 in more detail, the outermost layer 2 and the barrier layer 3 are adhered to each other by an outer adhesive layer 5 disposed between the layers 2, 3, and the barrier layer 3 and the sealant layer 4 are adhered to each other by an inner adhesive layer 6 disposed between the layers 3, 4.
[0026] The outermost layer 2 is also called the base layer of the packaging material 1, and is made of at least one material selected from the group consisting of a polyamide film, a polyester film, and a polyolefin film.
[0027] As the polyamide film, a biaxially oriented nylon film (for example, a biaxially oriented nylon 6 film) or the like is preferably used.
[0028] Examples of polyester films that can be used include polyethylene terephthalate films (PET films), polyethylene naphthalate films (PEN films), and polybutylene terephthalate films (PBT films).
[0029] As the polyolefin film, polypropylene films such as biaxially oriented polypropylene film (OPP film), polyethylene films, and the like are used.
[0030] The thickness of the outermost layer 2 is not limited, and is usually in the range of 10 to 50 μm.
[0031] The barrier layer 3 is usually made of a metal foil. Examples of the metal foil include aluminum (including its alloys), copper (including its alloys), nickel (including its alloys), titanium (including its alloys), and stainless steel foils, with aluminum foil being particularly preferred. The metal foil may have a corrosion prevention treatment layer (not shown) such as a chemical conversion coating formed on one or both sides.
[0032] The thickness of the barrier layer 3 is not limited, but is usually in the range of 5 to 50 μm, and preferably in the range of 10 to 40 μm.
[0033] The sealant layer 4 is made of a polypropylene film, a polyethylene film, etc. As the polypropylene film, a non-oriented polypropylene film (CPP film) or the like is used. As the polyethylene film, a linear low-density polyethylene film (LLDPE film) or the like is used.
[0034] The adhesive for the outer adhesive layer 5 is not limited as long as it can bond the outermost layer 2 and the barrier layer 3, and it is particularly preferable to use a two-component curing urethane adhesive as the adhesive, since the two-component curing urethane adhesive has high water resistance, high weather resistance, etc.
[0035] The outer adhesive layer 5 is formed, for example, by applying the adhesive of the outer adhesive layer 5 onto the barrier layer 3 (more specifically, the surface of the barrier layer 3 facing the outermost layer 2), which is the layer to be adhered to the outermost layer 2, by a predetermined application method.
[0036] The adhesive coating method for the outer adhesive layer 5 (i.e., the method for forming the outer adhesive layer 5) may be a gravure coating method, a spray coating method, a doctor blade coating method, or the like, and it is particularly preferable to use the gravure coating method, for the following reasons.
[0037] That is, in the gravure coating method, pattern coating is usually performed using a gravure roll engraved with a predetermined mesh number and depth on the surface. Therefore, by applying adhesive to the barrier layer 3 by the gravure coating method, the surface 5a of the outer adhesive layer 5 facing the outermost layer 2 is formed with regularly aligned fine irregularities as shown in FIG. 1. Then, when the outermost layer 2 is bonded to this surface 5a, the fine irregularities formed on this surface 5a are reflected on the surface 2a of the outermost layer 2. As a result, the uneven parts formed on this surface 5a and the uneven parts formed on the surface 2a of the outermost layer coincide with each other. This ensures that the surface of the exterior material 1, which is the surface 2a of the outermost layer 2, has the predetermined surface properties.
[0038] The adhesive for the inner adhesive layer 6 is not limited as long as it can bond the barrier layer 3 and the sealant layer 4, and a thermosetting acid-modified polypropylene adhesive or the like is used as the adhesive.
[0039] The method of applying the adhesive to the inner adhesive layer 6 (i.e., the method of forming the inner adhesive layer 6) is not limited, and the adhesive application method may be the gravure coating method, spray coating method, doctor blade coating method, or the like, as described above.
[0040] In this embodiment, the exterior packaging material 1 satisfies the first requirement that the surface quality of the surface 2a of the outermost layer 2 has an arithmetic mean height Sa in the range of 0.03 to 0.20 μm, and a cross-sectional area at a height position of +0.1 μm from the reference plane of Sa is 7500 μm. 2 If a convex portion having a height of 8 or more is defined as a peak 8 (see Figure 2), the number of peaks 8 is 1 mm 2 The second requirement is that the number of particles per one particle is in the range of 5 to 30. The surface texture is measured in accordance with ISO 25178.
[0041] By satisfying the first and second requirements, the surface 2a of the outermost layer 2 has high slipperiness, and since the contact area with the adhesive tape is large, the surface 2a of the outermost layer 2 also has high adhesion with the adhesive tape. Therefore, the lithium ion battery can be firmly fixed in position with the adhesive tape.
[0042] Furthermore, when the center of gravity (centre position) of the cross section at a height position of +0.1 μm from the reference plane of Sa in the peak 8 is defined as the center of gravity C of the peak 8 (see FIG. 3), the exterior material 1 is 1 mm 2 It is desirable that the third requirement be satisfied, that is, that the distances between the center-of-gravity positions C of adjacent peaks 8 present on the surface be all within a range of 150 to 700 μm.
[0043] By satisfying the third requirement, the slipperiness of the surface 2a of the outermost layer 2 can be reliably increased, and the contact area with the adhesive tape can be reliably increased, so that the adhesion of the surface 2a of the outermost layer 2 to the adhesive tape can also be reliably increased. Therefore, the lithium ion battery can be reliably and firmly fixed in position with the adhesive tape.
[0044] Here, the second and third requirements will be described with reference to FIGS. 2 and 3 as follows.
[0045] FIG. 2 is a schematic diagram showing contour lines at a height of +0.1 μm from the reference plane Sa in a surface unevenness image of the surface 2 a of the outermost layer 2 .
[0046] In the second requirement, the reference plane of Sa is the plane of the average height of the measurement area of the surface 2a of the outermost layer 2. The cross-sectional area at a height of +0.1 μm from the reference plane is the area surrounded by the contour line at a height of +0.1 μm from the reference plane. 2 A convex portion having a height of 1 mm or more is defined as a peak 8. 2 " is a square area S of 1 mm in the X direction and 1 mm in the Y direction perpendicular to each other in the measurement area. In the case of FIG. 2, the number of peaks 8 is eight.
[0047] In addition, 1 mm 2 Regarding the mountains that exist across the outer boundary line 10 of the square region S, the mountains whose center of gravity C exists inside or on the outer boundary line 10 are to be removed within 1 mm 2The number of peaks that exist on the outer boundary line 10 is counted, and the peaks that exist on the outer boundary line 10 are counted by 1 mm. 2 They do not count towards the number of mountains that exist.
[0048] FIG. 3 is a diagram for explaining the distance between the positions C of the centers of gravity of adjacent mountains 8 in the schematic diagram shown in FIG.
[0049] In the case of the distribution of the peaks 8 shown in the figure, the third requirement is met when the peaks are within 1 mm 2 This means that for all mountains 8 (that is, eight mountains 8) present in the square region S, the distances d1 to d11 between the center-of-gravity positions C of adjacent mountains 8 are all in the range of 150 to 700 μm.
[0050] Although the embodiment of the present invention has been described above, the present invention is not limited to the above embodiment, and various modifications can be made without departing from the gist of the present invention.
[0051] Furthermore, the exterior material for an electricity storage device according to the present invention is not limited to being used for lithium ion batteries, but may be used for other electricity storage devices, such as a lithium ion capacitor or an electric double layer capacitor. EXAMPLES
[0052] Specific examples and comparative examples of the present invention are shown below, but the present invention is not limited to the following examples.
[0053] <Example 1> A biaxially oriented 6 nylon film (thickness 25 μm) was prepared as the film forming the outermost layer 2, an aluminum foil (thickness 35 μm) was prepared as the metal foil forming the barrier layer 3, and an unoriented polypropylene film (thickness 30 μm) was prepared as the film forming the sealant layer 4.
[0054] A chemical conversion coating was formed on both sides of an aluminum foil (barrier layer 3). The formation method is as follows: a chemical conversion treatment liquid containing phosphoric acid, polyacrylic acid (acrylic resin), a chromium (III) salt compound, water and alcohol was applied to both sides of the aluminum foil and dried at 180°C, thereby forming a chemical conversion coating. The amount of chromium attached in the chemical conversion coating was 10 mg / m 2 It was.
[0055] Next, a two-component curing urethane adhesive as the adhesive for the outer adhesive layer 5 was applied to one side of the aluminum foil by gravure coating and dried. In this way, the outer adhesive layer 5 was formed on one side of the aluminum foil. The coating amount of the adhesive after drying was 3.5 g / m 2 It was.
[0056] In the above-mentioned gravure coating method, a gravure roll was used, the surface of which was engraved with a lattice pattern having a mesh number of 85 and a depth of 120 μm.
[0057] Then, the aluminum foil and the biaxially oriented nylon 6 film (outermost layer 2 ) were temporarily bonded with an outer adhesive layer 5 .
[0058] Next, a thermosetting acid-modified polypropylene adhesive was applied to the other side of the aluminum foil as the adhesive for the inner adhesive layer 6 and dried. In this way, the inner adhesive layer 6 was formed on the other side of the aluminum foil. The amount of the adhesive applied after drying was 2.5 g / m 2 It was.
[0059] Then, the aluminum foil and the unstretched polypropylene film (sealant layer 4) were temporarily bonded with the inner adhesive layer 6. This resulted in an exterior material having an outermost layer 2 made of a biaxially oriented 6 nylon film, a barrier layer 3 made of an aluminum foil, and a sealant layer 4 made of an unstretched polypropylene film in a laminated state.
[0060] Next, the exterior material was subjected to a heat aging treatment under the condition of being left to stand in an environment of 40°C for 9 days, thereby simultaneously curing the outer adhesive layer 5 and the inner adhesive layer 6. As a result, the outermost layer 2 and the barrier layer 3 were permanently bonded by the outer adhesive layer 5, and the barrier layer 3 and the sealant layer 4 were permanently bonded by the inner adhesive layer 6.
[0061] By the above method, a lithium ion battery outer casing material 1 was obtained.
[0062] <Examples 2 to 7 and Comparative Examples 1 to 4> Exterior materials 1 were obtained in the same manner as in Example 1 above, by varying the thickness of the outermost layer (biaxially oriented 6 nylon film) 2 and the number and depth of meshes formed on the surface of the gravure roll.
[0063] For each of the exterior packaging materials 1 of Examples 1 to 7 and Comparative Examples 1 to 4, the surface properties of the surface 2a of the outermost layer 2 were measured, the adhesion of the surface 2a of the outermost layer 2 to an adhesive tape was examined, and the dynamic friction coefficient of the surface 2a of the outermost layer 2 was measured to evaluate the slipperiness of the surface 2a of the outermost layer 2. The results are summarized in Table 1.
[0064] [Table 1]
[0065] In the "Material" column of "Outermost layer" in Table 1, "Ny" means biaxially oriented nylon 6 film.
[0066] Measurement of surface properties, evaluation of adhesion to adhesive tape, and measurement of dynamic friction coefficient (slipperiness) were carried out as follows.
[0067] <<Surface texture>> The surface 2a of the outermost layer 2 of the exterior material 1 is measured for its surface quality in accordance with ISO 25178, and the arithmetic mean height Sa is measured for 1 mm 2 Number of ridges per 1mm 2The distance between the positions C of the centers of gravity of adjacent peaks 8 present on the substrate 1 was measured. The measurement conditions and method were as follows.
[0068] A square sample measuring 10 mm in length and 10 mm in width was cut out from the exterior material 1. The surface properties of the sample were measured at random locations using a scanning white light interference microscope (Hitachi High-Technologies Corporation, "VS1330"). The lens used for this measurement was a two-beam interference objective lens 5x, and the wavelength filter was 520 nm.
[0069] The values in the "minimum distance dmin" and "maximum distance dmax" columns in Table 1 are 1 mm 2 These mean the minimum distance dmin and the maximum distance dmax between the positions of the centers of gravity C of the mountains 8 that are adjacent to each other.
[0070] <<Adhesion to adhesive tape>> The adhesion of the surface 2a of the outermost layer 2 to an adhesive tape was examined under the following conditions and by the following method.
[0071] A test piece measuring 15 mm wide x 150 mm long was cut out from the exterior material 1. An adhesive tape (tesa 70415) with an adhesive strength of 13 N / cm was attached to the surface of the test piece along its length. The adhesive tape had a width of 5 mm and a length of 80 mm or more. A hand roll weighing 2 kgf was then run back and forth over the adhesive tape five times, and the tape was then left to stand at room temperature for one hour.
[0072] Next, a tensile tester, Strograph (AGS-5kNX) manufactured by Shimadzu Corporation, was used, and one chuck was used to clamp and fix the end of the test piece, while the other chuck was used to grip the end of the adhesive tape. Then, in accordance with JIS K6854-3 (1999), the peel strength was measured when peeled at 180° at a peel speed of 300 mm / min, and the value at which this measured value stabilized was taken as the adhesion strength (unit: N / 5 mm) between the surface 2a of the outermost layer 2 and the adhesive tape.
[0073] The evaluation criteria for the adhesion of the surface 2a of the outermost layer 2 to the adhesive tape were as follows: an adhesion strength with the adhesive tape of 6 N / 5 mm or more was rated as "◎ (very high)", an adhesion strength of 5 N / 5 mm or more but less than 6 N / 5 mm was rated as "○ (high)", and an adhesion strength of less than 5 N / 5 mm was rated as "× (low)".
[0074] <<Dynamic friction coefficient (slipperiness)>> In order to evaluate the slipperiness of the surface 2a of the outermost layer 2, the dynamic friction coefficient of the surface 2a of the outermost layer 2 was measured in accordance with JIS K7125 (1999).
[0075] As shown in Table 1, In the surface properties of the surface 2a of the outermost layer 2 of the packaging material 1 in Examples 1 to 7, the arithmetic mean height Sa was in the range of 0.03 to 0.20 μm, and 2 The distance between the center of gravity positions C of adjacent mountains 8 is in the range of 120 to 800 μm. The surface 2a of the outermost layer 2 of the packaging materials 1 in Examples 1 to 7 had a small dynamic friction coefficient and good slipperiness. Furthermore, the surface 2a of the outermost layer 2 of the packaging materials 1 in Examples 1 to 7 had high adhesion to an adhesive tape, and in particular, the surface 2a of the outermost layer 2 of the packaging materials 1 in Examples 1 to 6 had extremely high adhesion to an adhesive tape. [Industrial Applicability]
[0076] The present invention can be used as an exterior material for electricity storage devices (for example, lithium ion batteries, lithium ion capacitors, and electric double layer capacitors). [Explanation of symbols]
[0077] 1: Exterior material 2: Outermost layer 3: Barrier layer 4: Sealant layer 5:Outer adhesive layer 6: Inner adhesive layer 8: Mountain C: Center of gravity of the mountain
Claims
1. The present invention relates to a laminated structure including an outermost layer, a sealant layer, and a barrier layer disposed between the outermost layer and the sealant layer, An exterior material for an electricity storage device, which is used to package contents of an electricity storage device that is fixed in position with an insulating adhesive tape, comprising: the outermost layer is made of a film, In terms of surface properties of the outermost layer, The arithmetic mean height Sa is in the range of 0.03 to 0.20 μm, When a convex portion having a cross-sectional area of 7500 μm2 or more at a height position of +0.1 μm from the reference plane of Sa is defined as a peak, and further, the center of gravity of a cross section of the peak at a height position of +0.1 μm from the reference plane is defined as the center of gravity of the peak, the distance between the center of gravity of adjacent peaks present within 1 mm2 is all within the range of 120 to 800 μm.
2. In terms of surface properties of the outermost layer, The number of peaks is 1 mm 2 2. The exterior packaging material for an electricity storage device according to claim 1, wherein the number of particles per one particle is in the range of 5 to 30.
3. The contents of an electricity storage device are packaged in the exterior packaging material for an electricity storage device according to claim 1 or 2, An energy storage device fixed in place with insulating adhesive tape.
Citation Information
Patent Citations
Providing bore or cut in thin plate of metal or brittle material such as glass or quartz
JP1981052178A
Battery, method for manufacturing the same, battery unit, and battery module
JP2012113843A
Laminated body
JP2013006412A
External facing material for secondary battery and secondary battery
JP2013101764A
Laminate film for battery outer packaging and method for producing the same
JP2014026778A